Isoliquiritigenin Alleviates Periodontitis by Suppressing Inflammation via NF-κB Signaling Pathway of Immune Cell - Wang X; Zhao T; Liang B; Fang J; Dong Q; Chen Q (Journal of Inflammation Research)
Xiao Wang,1,2,* Tianliang Zhao,2,3,* Biling Liang,1 Jing Fang,4 Qiu Dong,5 Qianqian Chen1,2 1Department of Stomatology, The First Affiliated Hospital of Guangxi University of Science and Technology, Guangxi University of Science and Technology, Liuzhou, 545006, People’s Republic of China; 2Medical College, Medical Experimental Center, Guangxi University of Science and Technology, Liuzhou, 545006, People’s Republic of China; 3School of Public Health, Youjiang Medical College for Nationalities, Baise, 533000, People’s Republic of China; 4Hangzhou Tigermed Consulting Co., Ltd, Hangzhou, 310051, People’s Republic of China; 5Centre for Bone, Joint and Sports Medicine, The First Affiliated Hospital of Jinan University, Guangzhou, 510000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qianqian Chen; Qiu Dong, Email 18221767137@163.com; dong1005@stu2019.jnu.edu.cnBackground: Periodontitis, a chronic infectious disease, presents significant treatment challenges due to antibiotic resistance and high recurrence rates, necessitating novel therapeutics.Methods: Network pharmacology identified ISL’s potential targets in periodontitis, focusing on NF-κB signaling pathway. Toxicity was assessed via MTT assay and long-term toxicity studies in vivo. Anti-inflammatory effects were evaluated using enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry (IHC), while antibacterial activity was tested in vivo. Micro-computed Tomography (Micro-CT) and hematoxylin and eosin (H&E) staining analyzed periodontal tissue recovery. Western blotting measured NF-κB-p65 and IκB phosphorylation. Molecular docking and dynamics simulations explored ISL’s targets.Results: ISL exhibited low toxicity and reduced IL-6, IL-1β, and TNF-α levels in vitro and in vivo. It demonstrated strong antibacterial effects and mitigated alveolar bone loss. Phosphorylation of NF-κB-p65 and IκB decreased in immune cells, with IKKB (– 8.4 docking score) identified as a stable target.Conclusion: ISL effectively treats periodontitis by combining antibacterial and anti-inflammatory actions, targeting IKKB to suppress NF-κB signaling pathway. This study highlights ISL’s therapeutic potential and provides a foundation for developing periodontitis treatments.Keywords: periodontitis, isoliquiritigenin, network pharmacology, NF-κB signaling pathway